Effects of Exergames and Resistance Training on Well-Being in Older Adults: A Randomized Clinical Trial - Vandrize Meneghini; Eduardo Hauser; Camilo Luis Monteiro Lourenço; Aline Rodrigues Barbosa (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To analyze the effects of an exergame-based training compared to resistance training on the quality of life and symptoms of depression in older adults. METHODS: This was a two-arm, non-blinded, randomized clinical trial. Thirty-five participants (62.09 ± 7.11 years) were randomized either on the Exergame-based Training Group (n = 17) or the Resistance Training Group (n = 18). Sessions lasted 50 to 60 minutes, three times per week, for 13 weeks. For the Exergame-based Training Group, we used games that simulate sports and adventure activities through Xbox360 Kinect™. The Resistance Training Group performed ten exercises per session for upper and lower limbs using free weights and machines, following linear periodization and individualized loads. Quality of life and symptoms of depression were assessed using the World Health Organization Quality of Life assessment - an abbreviated version (WHOQOL-BREF) and the Geriatric Depression Scale, respectively. We performed a two-way analysis of variance (p ≤ 0.05). RESULTS: Only time effects were identified for overall quality of life, general health, and symptoms of depression. After the intervention, overall quality of life score increased (3.82 ± 0.95 versus 4.18 ± 0.53, p = 0.05), whereas symptoms of depression decreased (3.35 ± 1.73 versus 2.59 ± 1.54, p = 0.02) in the Exergame-based Training Group, and the general health improved in the Resistance Training Group (3.78 ± 0.81 versus 4.11 ± 0.68, p = 0.05) compared with the baseline scores. CONCLUSION: Both training groups improved different aspects of quality of life. The Exergaming-based Training Group improved the overall perception, whereas the Resistance Training Group improved the general health-related perception. Participants in the Exergame-based Training Group also decreased the number of symptoms of depression.